2023
DOI: 10.1186/s12884-023-05712-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of partial and adequate maternal health services utilization in Nigeria: analysis of cross-sectional survey

Abstract: Background Access to health services during pregnancy, childbirth and the period after birth provides a substantial opportunity to limit cases of maternal mortality. In sub-Saharan Africa, the proportions of women who utilize health services remain below 70%. This study examined the factors associated with partial and adequate maternal health services utilization in Nigeria. Methods This paper used data from 2018 Nigeria Demographic and Health Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This can be done during ante-natal care services which record an increasing number of women in attendance according to studies by [ 6 , 31 ]. This finding corroborates with existing literatures by [ 1 ] and [ 20 ] on the essence of health education during ante-natal care as a measure in achieving maternal healthcare service utilization for rural women in Nigeria.…”
Section: Discussionsupporting
confidence: 92%
“…This can be done during ante-natal care services which record an increasing number of women in attendance according to studies by [ 6 , 31 ]. This finding corroborates with existing literatures by [ 1 ] and [ 20 ] on the essence of health education during ante-natal care as a measure in achieving maternal healthcare service utilization for rural women in Nigeria.…”
Section: Discussionsupporting
confidence: 92%
“…This irregular availability of family planning medications, especially in rural areas, would be detrimental to the timeliness required for the emergency usage of these drugs were necessary. On the other hand, limited utilization of antenatal services due to the place of residence was also identified when NDHS data from 2013-2018 was systematically analyzed [ 25 ]. Another study showed that about 25% of women in Benue State spend more than 30 minutes before arriving at their nearest health facility [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome variable was then further divided into three categories: not utilized (for those who used none of the three services); partially utilized (for those who used one or two of the services); and adequately utilized (for those who used all of the services). Previous studies employed similar classification approaches, as of ‘no’, ‘partial’, and ‘adequate’ service uptake [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%